Tetraneura (Tetraneurella) nigriabdominalis (Hemiptera: Aphidoidea) – a species extending its range in Europe, and morphological comparison with Tetraneura (Tetraneura) ulmi - Walczak, Urszula; Borowiak-Sobkowiak, Beata; Wilkaniec, Barbara (Entomologica Fennica, 2017)
The paper presents the first records of Tetraneura (Tetraneurella) nigriabdominalis (Sasaki, 1899) (Eriosomatinae, Eriosomatini) from Poland, an alien species that has been expanding its range northward, which is presumably connected with climate warming. Secondary hosts of this aphid are different plant species from the family Poaceae, including Zea L. Considering the steady increase in maize cultivation area in Europe, the species can become a potential threat to this cereal. We present the morphological characteristics of winged morphs developing in galls on trees from the genus Ulmus L. Those characteristics enable to distinguish this species from Tetraneura (Tetraneura) ulmi (Linnaeus, 1758), which dominates on elms in northwestern Europe. The data on the distribution of T. (T.) nigriabdominalis in Europe are also provided.